An Investigation on Mechanical and Microstructural Properties of Porous Nickel-Based Alloy Fabricated by Investment Casting as an Implant Materials - Er, Yusuf (My University, 2021)
In this study, Nickel-Chrome-Molybdenum alloy is manufactured using investment casting method with centrifugal casting device from a polyurethane foam model in a regular and open- pore form, as a hard tissue implant. The samples produced have 10, 20, and 30 (±3) pores per inch and 0.0008, 0.0017, and 0.0027 g/mm3 densities, respectively. Young’s modulus, hardness and mechanical behaviors of the samples were investigated by SEM, EDS and compressive test. As a result, it is seen that the pore size and the pore wire diameter of the samples could be controlled thus compression strength and young modulus. In this way it was understood that an implant material could be produced with similar mechanical properties to the human bone.
Keywords: Metal foams Biomaterials Mechanical properties Investment casting Nickel-Chrome-Molybdenum